Representing ocean biology-induced heating effects in ROMS-based simulations for the Indo-Pacific Ocean - Zhang, Wenzhe; Gao, Chuan; Tian, Feng; Yu, Yang; Wang, Hongna; Zhang, Rong-Hua (Frontiers in Marine Science, 2024)
Incident shortwave radiation can penetrate and heat the upper ocean water column, acting to modulate the stratification, vertical mixing and sea surface temperature. As a light-absorbing constituent, ocean chlorophyll (CHL) plays an important role in regulating these processes; however, its heating effect on the ocean state remains controversial and exhibits strong model dependence on ways the solar radiation transmission and the related CHL-induced heating are represented. In this study, we implement a chlorophyll-based two-way coupling between physical and ecological processes within the Regional Ocean Modeling System (ROMS). The bio-physics coupled model performs well in simulating the structure and variability of oceanic physical and ecological fields in the tropical Indo-Pacific region. Three CHL-related heating terms are analyzed based on the model output to diagnose the ocean biology-induced heating effects, namely the shortwave radiation part penetrating out of the base of the mixed layer (ML; Qpen), the portion absorbed within the ML (Qabs), and the rate of temperature change of the ML resulting from the Qabs effects (Rsr). Results show that the spatio-temporal distributions of the three heating terms are mainly determined by the ML depth (MLD). However, Qpen can also be regulated by the euphotic depth (ED), especially in the western-central equatorial Pacific. This moderating effect is particularly evident during El Niño when the ED tends to be greater than the MLD; positive ED anomalies act to enhance the positive Qpen anomalies caused by negative MLD anomalies. For the first time, the bio-heating effects are quantified within the ROMS-based two-way coupling context between the physical submodel and ecological submodel over the tropical Indo-Pacific Ocean, providing a basis for further understanding of the bio-effects and mechanisms. It is expected that the methodology and understanding developed in this study can help explore the chlorophyll-related processes in the ocean and the interactions with the atmosphere.